EFEKTIVITAS MODEL PJBL BERBANTUAN E-MODUL BERBASIS FLIPBOOK UNTUK MENINGKATKAN HASIL BELAJAR IPAS DI SEKOLAH DASAR - Sari, Sinta Nela Mukti; Isdaryani, Barokah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education in the current era demands to be in line with the times and technology that continues to innovate. There are efforts that can be taken, namely innovating the media and teaching models that are applied in line with the characteristics of students. Efforts made are to develop media and learning models according to the characteristics of students, such as e-module flipbooks assisted by the Project Based Learning model. Experimental research with a Nonequivalent Control Group Design was conducted to test the effectiveness of the model in improving elementary science learning outcomes in the Pesertanta Pentas Cluster. The population taken was grade IV SDN Bagusan (experimental class) and SDN Plumbon (control class). Data analysis using SPSS 25 showed an increase of 28.19 in the experimental class and 19.64 in the control class. The results of the Paired simples T-test post-test test resulted in t-count> t-table and sig <0.05 so that Ha is accepted. The N-gain test results of 68.32% indicate that the model is quite effective in improving the science learning outcomes of fourth grade elementary school students in Gugus Pentas Pesertanta, Temanggung.